RANCANG BANGUN SISTEM INFORMASI PENJUALAN MINI MARKET HUTASOIT BERBASIS WEB - Silaban, Tutur Martabe; Syastra, Muhamad Taufik (LPPM Universitas Putera Batam, 2019)
Internet users in Indonesia experienced a significant increase, namely from the total Indonesian population in 2017 amounting to 262 Million People and Internet users 143.26 Million, while in 2018 there was an increase in population and Internet users, with a total population of 264,16 Million People and Internet users 171.17 million. The use of the internet to merchants has reached a maximum percentage of 100%, so it can be concluded to buy and sell in 2018 the population in Indonesia is more utilizing online information media. Web-based media is one of the technological solutions that can be implemented for the process of selling goods. With the existence of information technology, it can be developed in any field according to user needs. The information system developed is a web-assisted information system, android. In the study there are several stages that must be completed and these stages refer to existing theories in previous studies is to use the Waterfall method which consists of Analysis, Design, Coding, and Testing. SDLC is a stage in developing or editing a software system by implementing models and methods that people use in developing previous software based on best practice or well-tested ways. With opportunities like this, the internet can be used as a platform to build a system, specifically for the sales system at the Minimarket Hutasoit.